STUDY AND PERFORMANCE OF PARTIAL DISCHARGE OF MODEL FOR DIFFERENT TYPE INSULATION MATERIALS WITH CAPACITANCE VALUE - Baghelkar, Neetu; Dubey, Abhishek (International Journal of Research -GRANTHAALAYAH, 2021)
The properties of the insulating material must be the best to avoid failure of electrical equipment. Partial discharges act as electrical sparks that occur within insulation and the high-voltage electrical system. The different types of voltage and current pulses are produced, which last for a very short time. Partial discharge is taking place in high voltage power equipment such as cables, transmission lines and transformers, etc.